The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1002/1097-0142(197607)38:1<273::aid-cncr2820380141>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced xerostomia in cancer patients.Effect on salivary and serum electrolytes

Abstract: Saliva and serum electrolyte concentrations were monitored in 30 patients given a course of xerostomia-producing cancer radiotherapy. The mean flow r a t e of stimulated whole saliva decreased 83.3% during a 6-week treatment period. The striking reduction in saliva o u t p u t was accompanied by significant increases in saliva Na+, C1-, Cat+, Mg" and Prot.-concentrations and by a decrease i n saliva HCO; content. The xerostomic saliva was more concentrated and had a greater salinity t h a n t h e pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
10

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(61 citation statements)
references
References 12 publications
3
47
1
10
Order By: Relevance
“…Xerostomia can result in long-term or even permanent oral function impairment and usually is associated with morbidity that profoundly affects the quality of life. [1][2][3][4] Several potential methods for preventing radiation-induced xerostomia have been described; however, xerostomia management is complex and often is refractory to most interventions. 5 Studies using systemic sialogogues (e.g., pilocarpine) concomitant with RT have failed to show significant maintenance of saliva production.…”
Section: Introductionmentioning
confidence: 99%
“…Xerostomia can result in long-term or even permanent oral function impairment and usually is associated with morbidity that profoundly affects the quality of life. [1][2][3][4] Several potential methods for preventing radiation-induced xerostomia have been described; however, xerostomia management is complex and often is refractory to most interventions. 5 Studies using systemic sialogogues (e.g., pilocarpine) concomitant with RT have failed to show significant maintenance of saliva production.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Using a rat model in this study, we showed that HSP25 and HSP70i protected radiation-induced submandibular damage and that this protective effect was attributable to inhibition of cell death and restoration of saliva fluid.…”
Section: Discussionmentioning
confidence: 99%
“…b Entwicklungsstö-rungen der Zähne nach Bestrahlung. Frontzähne überkront, Restbezahnung hypoplastisch und kariesanfällig eine geringe Speichelflussrate generell mit einem erhöhten Kariesrisiko assoziiert ist [2,12]. Diese Beobachtungen unterstützen die These, welche die Hyposalivation mitsamt ihren Folgen als Ursache für die rasche Zerstörung der Zähne bei bestrahlten Patienten sieht.…”
Section: Speichelflussunclassified